"Mohsite" of Colomba: Identification as Dessauite-(Y). (10th April 2014) - Bittarello, Erica; Ciriotti, Marco E.; Costa, Emanuele; Gallo, Lorenzo Mariano
Abstract : During a reorganization of the mineralogical collection of Turin University, old samples of the so-called mohsite of Colomba were found. "Mohsite" was discredited in 1979 by Kelly et al., as a result of some analyses performed on the equivalent material coming from the French region of Hautes-Alpes, but the original samples found in similar geological setting in Italy were lost and never analysed with modern equipment. After more than a century, the rediscovered samples of Professor Colomba were analysed by means of SEM-EDS analysis, microRaman spectroscopy, and X-ray diffraction. The results have demonstrated that the historical samples studied by Colomba are Pb-free dessauite-(Y), and pointed to an idealized crystal chemical formula (Sr0.70 Na0.25 Ca0.09 )Σ=1.04 (Y0.62 U0.18 Yb0.09 Sc0.08 )Σ=0.97 F e 2 2 + (Ti12.66 F e 4.78 3 + V 0.26 3 + )Σ=17.70 O38 and unit-cell parameters a = 10.376(3) Å, c = 20.903(6) Å, and V = 1949(1) Å 3 .